Rural women in agriculture and food security - Loayza Alatrista, Sulema (2017)
Here we analyze female peasants participation in agricultural and food activities, their relationship and involvement in the market, protagonist role on food security strategies of small farmer communities in the south part of the Andes, which is one of the main food providers for the communities, in the context of world commerce and the economic boom of Andean food. This study was done with peasant communities, farming multiple crops, in the Andean valleys of Arequipa and Cusco.